Indians in Pensamiento Gonzalo: The Influence of 20th-Century Peruvian Intelligentsia on Shining Path's Ideology (2020)
During the last decades of the 20th century, Shining Path conceived Indian culture mainly as part of feudalist-capitalist alienation. Consequently, this insurrectionist organization aimed to mobilize the indigenous communities around a classoriented revolutionary project. Although the academic literature has acknowledged and studied this process, its historical roots in the intelligentsia of the early 20th century remain under-examined. To contribute to their research, this article first analyzes the “neo-indigenist and indigenist discussion” of the first decades of the century, mainly through the works of Manuel González Prada, Luis Eduardo Valcárcel, and José Uriel García. The article will then focus on José Carlos Mariátegui and Víctor Raúl Haya de la Torre to explore the discussion around the implementation of socialist thought in Peru. Finally, this research analyzes the influence of the previous authors on the configuration of Shining Path’s ideology, Pensamiento Gonzalo. The article argues that Shining Path intensified three tendencies of the 20th-century Peruvian intelligentsia: the need to assist Indians in the development of an effective discourse, the legitimation of revolutionary violence, and the Peruvian bourgeoisie’s leadership of the Indians. In conclusion, Shining Path’s ideology should not be regarded as a rara avis, but as the result of a dogmatic application of Maoism to already existing discussions of the Indian problem. Keywords Shining Path, Peru, socialism, Indians, peasants, Pensamiento Gonzalo